Perspectives in Implementing a Pragmatic Pediatric Primary Care–Based Intervention Trial - Pbert, Lori (Am J Prev Med, 2015)
The 2013 U.S. Preventive Services Task Force (USPSTF) concluded that behavioral interventions are effective in reducing initiation of smoking in youth, recommending primary care clinicians provide education or brief counseling to prevent initiation, and that there are promising trends toward behavioral interventions improving cessation in this population. Our primary care–based intervention RCT conducted between 2000 and 2004, Air It Out, informed these USPSTF recommendations. Our trial was designed to determine whether a pediatric primary care practice–based smoking prevention and cessation intervention would be effective in increasing abstinence rates among adolescents under usual clinic conditions, to inform clinical practice. Therefore, the trial was designed to be largely a pragmatic trial. In this paper, we describe where each of the Air It Out study components falls along the pragmatic–explanatory continuum regarding participant eligibility criteria, intervention and comparison condition design, follow-up and outcomes, compliance and adherence assessments, and analysis. Such an assessment assists researchers by providing a framework to guide decisions regarding study design and implementation. We then share a few principles and lessons learned in developing and implementing the primary care–based intervention trial, focusing on study setting selection, engaging providers who will be delivering the intervention and the target population who will be receiving it in designing the trial and interventions to be tested, and the need to carefully plan recruitment and retention procedures. The hope is to increase the number of well-designed studies that can be included in the evidence reviews to guide future USPSTF recommendation statements.